Association study of CCR6 rs3093024 with Rheumatoid Arthritis in a Pakistani cohort - Akhtar, Mehran (Saudi J Biol Sci, 2020)
C-C Chemokine receptor 6 (CCR6), an important protein in inflammatory and immunological responses, has been previously reported to be associated with rheumatoid arthritis (RA). Therefore, in order to replicate these findings, a case-control study was conducted on 500 subjects (including 250 RA patients and 250 healthy controls) of Pakistani origin. The aim of this study was to determine the association of CCR6 rs3093024 variant with RA and identify its role in splicing events using bioinformatics tools. The clinical and demographic characteristics of the patients were collected using a well-designed questionnaire. The genotype frequencies of CCR6 rs3093024 variant were determined using tetra-primer ARMS-PCR (amplification of refractory mutation system-polymerase chain reaction) method. A significant difference was found between CCR6 rs3093024 genotype frequencies [P = 0.0016, χ(2) = 12.915]. Similarly, a significant difference in the allele frequencies between RA patients and healthy controls was also observed [P = 0.0003 and OR (95% CI) = 0.63 (0.49–0.80)]. The stratification of patients showed that there was a significant increase in AA genotype against AG + GG in patients [P = 0.0014, OR (95% CI) = 2.0 (1.32–3.02)]. Furthermore, using bioinformatics analysis, it was found that CCR6 rs3093024 variant might create a potential splicing enhancer motif (SF2/ASF (IgM-BRCA1) with score of 77.92; Threshold 70.53), which might have important impact on the product of this gene. This study suggests that the A variant of CCR6 rs3093024 variant is significantly associated with RA-risk and its G variant is protective in Pakistani population but a multi-cohort large sized population study is needed to elucidate these results. Moreover, functional studies are needed to highlight the effects of this polymorphism on the function of CCR6 gene.